Arthroscopic management of rockwood type V acromioclavicular joint dislocation using a modified suture-passage technique with a four-leaf clover plate and adjustable loop plate: a case report - Zhou, Dejie; Qi, Xingyong; Liu, Xinwei; Li, Yaqin; Liu, Bo; Zhou, Yongwen; Liu, Hantao; Zhang, Fan; Zhao, Lianghu; Liu, Cai (Frontiers in Surgery, 2025)
IntroductionAcromioclavicular (AC) joint dislocation is a prevalent shoulder injury that, if not treated promptly and appropriately, can cause persistent pain and functional impairment. Numerous surgical techniques have been described, but no universally accepted gold standard exists. Arthroscopic coracoclavicular fixation with a TightRope has gained popularity owing to its minimally invasive approach, enhanced visualization, reliable mechanical stability, and ability to replicate coracoclavicular ligament biomechanics. However, potential complications such as coracoid or clavicular fractures remain concerns.Case presentationA 63-year-old male was admitted 12 days after a fall, presenting with left shoulder pain and limited mobility. Physical examination revealed marked superior displacement of the distal clavicle, a positive piano-key sign, and no significant anteroposterior translation. Radiographs confirmed a Rockwood type V AC joint dislocation. Arthroscopic coracoclavicular fixation was performed using a modified suture-passage technique with a four-leaf clover plate and an adjustable loop plate (ALP). At three months, the patient had resumed normal activities. Though clavicular tunnel enlargement was detected at 3 months and showed slight progressed by 6 months, it subsequently stabilized thereafter without any consequence at one-year follow-up. Only a minor loss of acromioclavicular joint reduction was observed, and the patient remained asymptomatic with good functional recovery.ConclusionsThis modified arthroscopic technique using a four-leaf clover plate with an ALP showed favorable short-term outcomes in AC joint dislocation. Further studies are required to confirm its long-term safety and effectiveness.